Real‑life cost and cost‑effectiveness for tiotropium 18 μg od monotherapy in moderate and severe COPD patients: a 48‑month survey - Povero, Massimiliano; Pradelli, Lorenzo; Turco, Paola; Dal Negro, Roberto Walter (Farmeconomia. Health economics and therapeutic pathways, 2014)
BACKGROUND: Tiotropium monotherapy enables a significant minimization of morbidity in COPD. OBJECTIVE: to evaluate and compare cost and cost‑effectiveness of tiotropium monotherapy administrated for 24 months (18 μg od) in mild‑to‑moderate and severe chronic obstructive pulmonary disease (COPD). METHODS: Clinical outcomes (days in hospital; visits in general ward; cycles of systemic steroids; cycles of antibiotics and maintenance therapy drugs) were evaluated in two groups of patients corresponding to predicted FEV1 baseline values ≤ 50% (A) and > 50% (B) from the Italian NHS perspective. In order to perform cost‑effectiveness analysis, FEV1 value, available for each patient, was converted in SGRQ score using a published multivariate linear model. Utilities were then obtained through the Ståhl equation. RESULTS: The comparison between 24 months of standard therapy and subsequent 24‑month period of tiotropium monotherapy showed that hospitalization cost, which represents the driving treatment cost, drops from 77% to 69% (A) and from 67% to 33% (B) of the total cost. Differently, maintenance therapy cost increased but the amount was more than offset by the savings accruing from the shortening of hospitalization. Furthermore, cost‑effectiveness results revealed a mean savings of about 216 € (A) and 961 € (B) other than a mean gain of 0.07 QALY (A) and 0.02 QALY (B). Dominance of tiotropium (calculated only within patients completing treatment course) revealed that in almost 29% (A) and 36% (B) of subjects tiotropium strategy is dominant while only in 2% (A) and 7% (B) of cases is associated to costs increment and worsening on quality of life. The dominance was systematic in severe COPD. Statistical analyses confirm such trend. CONCLUSIONS: Results of the present study suggest that tiotropium used as unique treatment in COPD systematically consents significant costs savings together with positive effects on evaluated quality. These effects prove proportional to COPD severity.